Use of Electrochemical Noise for the Study of Corrosion by Passivated CUSTOM 450 and AM 350 Stainless Steels - Almeraya Calderón, Facundo; Villegas Tovar, José Miguel; Lara Banda, María del Refugio; Jáquez Muñoz, Jesús Manuel; Estupiñan López, Francisco Humberto; Gaona Tiburcio, Citlalli (Molecular Diversity Preservation International, 2024)
Precipitation-hardening stainless steels, like AM 350 and Custom 450, are extensively utilized in various aerospace applications. The latter steel is utilized for applications needing great strength and corrosion resistance. In contrast, the former steel has a good corrosion resistance and moderate strength. The purpose of this study was to analyze transient frequencies in the electrochemical noise of Custom 450 and AM 350 stainless steels that had been passivated for 60 and 90 min at 25 and 49 °C using baths of citric and nitric acid and then immersed in solutions containing 1% sulfuric acid (H2SO4) and 5% sodium chloride (NaCl). The potentiodynamic polychromatic curves employed electrochemical techniques and noise (EN) based on the ASTM-G5 and G199 standards. Two methods of data analysis were applied concerning EN: the domain of frequencies (power spectral density, PSD) and the time–frequency domain (Hilbert-Huang Transform). The PHSS passivated in citric acid indicated current densities in the H2SO4 solution between 10−2 and 10−3 mA/cm2, while those in the NaCl solution were recorded around 10−4 and 10−5 mA/cm2. The citric acid functions as a passivating agent. The results of the electrochemical noise analysis show that the PHSS passivated in nitric acid displayed a greater corrosion resistance. Moreover, there is a tendency for PHSS to be passivated in nitric acid to corrode locally.